Agroecology for the realization of ecological rights (Papeles, 2022)
This paper raises the potential of agroecology as a strategy for the realization of ecological rights in Abya Yala. Based on a questioning of the socio-ecological impact of transnational corporations on the continent, the agroecological shift of the agri-food model is postulated as an authentic strategy for the realization of (socio-)ecological rights. It starts from a broad notion of the term ecology, which implies the coexistence between humans and non-humans. The concept of agroecology is recovered by its link to the local management of agri-food production. The disposal of foreign inputs - both seeds and agrochemicals - contributes not only to ecological sustainability, but also to social independence from transnational corporations. It also promotes the recovery of ancestral knowledge related to land and culture.
Keywords: Agroecology; ecological rights; socio-ecological transition; neo-extractivism; Abya Yala